Hepatocellular Carcinoma Presenting with Obstructive Jaundice during Pregnancy - Huan-wei Chen; Feng-jie Wang; Jie-yuan Li; Eric C. H. Lai; Wan Yee Lau (Case Reports in Surgery, 2014)
Introduction. Both hepatocellular carcinoma (HCC) presenting during pregnancy and HCC presenting with obstructive jaundice due to a tumor cast in the biliary tract are very rare. The management of these patients remains challenging. Presentation of Case. A 23-year-old lady presented with obstructive jaundice at 38 weeks of gestation. Investigations showed HCC with a biliary tumor thrombus. She received percutaneous transhepatic biliary drainage (PTBD) and caesarean section. Right hepatectomy, extrahepatic bile duct resection, and left hepaticojejunostomy were carried out when the jaundice improved. The postoperative course was uneventful. She was discharged home on postoperative day 10. Histopathology showed HCC with a tumor thrombus in the bile duct. The surgical margins were clear. One year after surgery, the mother was disease-free and the baby was well. Conclusion. With proper management, curative treatment is possible in a pregnant patient who presented with obstructive jaundice due to a biliary tumor thrombus from HCC.